Primary cilia: The central role in the electromagnetic field induced bone healing - Chen, Yangmengfan; Lu, Chao; Shang, Xifu; Wu, Kerong; Chen, Kun (Frontiers in Pharmacology, 2022)
Primary cilia have emerged as the cellular ‘antenna’ that can receive and transduce extracellular chemical/physical signals, thus playing an important role in regulating cellular activities. Although the electromagnetic field (EMF) is an effective treatment for bone fractures since 1978, however, the detailed mechanisms leading to such positive effect are still unclear. Therefore, primary cilia may play the central role in receiving EMF signals, translating physical signals into biochemical information, and initiating various signalling pathways to transduce signals into the nucleus. In this review, we elucidated the process of bone healing, the structure and function of primary cilia, as well as the application of EMF in the clinic. To comprehensively understand the process of bone healing, we used bioinformatics to analyse the molecular change and associated the results with other studies. Moreover, this review summarised some limitations in EMFs related research and provides an outlook for ongoing studies. In conclusion, this review illustrated the underlying mechanisms of primary cilia in the EMF induced bone healing process and will shed light on further studies.